Randomized clinical trial of therapeutic music video intervention for resilience outcomes in adolescents/young adults undergoing hematopoietic stem cell transplant: A report from the Children's Oncology Group. Issue 6 (27th January 2014) - Robb, Sheri L.; Burns, Debra S.; Stegenga, Kristin A.; Haut, Paul R.; Monahan, Patrick O.; Meza, Jane; Stump, Timothy E.; Cherven, Brooke O.; Docherty, Sharron L.; Hendricks‐Ferguson, Verna L.; Kintner, Eileen K.; Haight, Ann E.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND To reduce the risk of adjustment problems associated with hematopoietic stem cell transplant (HSCT) for adolescents/young adults (AYAs), we examined efficacy of a therapeutic music video (TMV) intervention delivered during the acute phase of HSCT to: 1) increase protective factors of spiritual perspective, social integration, family environment, courageous coping, and hope‐derived meaning; 2) decrease risk factors of illness‐related distress and defensive coping; and 3) increase outcomes of self‐transcendence and resilience. METHODS This was a multisite randomized, controlled trial (COG‐ANUR0631) conducted at 8 Children's Oncology Group sites involving 113 AYAs aged 11‐24 years undergoing myeloablative HSCT. Participants, randomized to the TMV or low‐dose control (audiobooks) group, completed 6 sessions over 3 weeks with a board‐certified music therapist. Variables were based on Haase's Resilience in Illness Model (RIM). Participants completed measures related to latent variables of illness‐related distress, social integration, spiritual perspective, family environment, coping, hope‐derived meaning, and resilience at baseline (T1), postintervention (T2), and 100 days posttransplant (T3). RESULTS At T2, the TMV group reported significantly better courageous coping (Effect Size [ES], 0.505; P = .030). At T3, the TMV group reported significantly better social integration (ES, 0.543; P = .028) and family environment (ES, 0.663; P = .008), as well as moderate nonsignificant effect sizes for spiritual perspective (ES, 0.450; P = .071) and self‐transcendence (ES, 0.424; P = .088). CONCLUSIONS The TMV intervention improves positive health outcomes of courageous coping, social integration, and family environment during a high‐risk cancer treatment. We recommend the TMV be examined in a broader population of AYAs with high‐risk cancers. Cancer 2014;120:909–917. © 2013 American Cancer Society.